Reduced pulmonary function, low-grade inflammation and increased risk of total and cardiovascular mortality in a general adult population: Prospective results from the Moli-sani study. (August 2021) - Costanzo, Simona; Magnacca, Sara; Bonaccio, Marialaura; Di Castelnuovo, Augusto; Piraino, Alessio; Cerletti, Chiara; de Gaetano, Giovanni; Donati, Maria Benedetta; Iacoviello, Licia; ,
Abstract: Aim: to investigate the relation of pulmonary function impairment with mortality and the possible mediation by low-grade inflammation in a general adult population. Methods: A prospective investigation was conducted on 14, 503 individuals from the Moli-sani study (apparently free from lung disease and acute inflammatory status at baseline; 2005–2010). The 2012 Global Lung Function Initiative percent predicted (% pred) value of forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), forced expiratory flow at 25–75% of FVC (FEF25-75) and FEV1 quotient (FEV1Q) index were used. C-reactive protein and blood cell counts were measured and a score of subclinical inflammation (INFLA-score) was calculated. Results: Over a median follow-up of 8.6y, 503 deaths (28.9% cardiovascular) were ascertained. Total mortality increased by 19% for each decrease in 1 standard deviation of FEV1% pred or FVC% pred (Hazard Ratio:1.19; 95% CI:1.11–1.28 and 1.19; 1.10–1.28, respectively). Comparable findings for FEV1Q (1.30; 1.15–1.47) were observed. A statistically significant increased risk in cardiovascular mortality of 23%, 32% and 49% was observed for 1 standard deviation decrease of FEV1% pred, FVC% pred and FEV1Q, respectively. INFLA-score mediated the association of FEV1% pred and FEV1Q with cardiovascular mortality by 22.3% and 20.1%, respectively. Subjects with FEV1, FVC lower than normal limit showed increased risk both in total and cardiovascular mortality. Abnormal FEF25-75 values were associated with 33% (1.33; 1.02–1.74) total mortality risk. Conclusions: Obstructive lung function impairment was associated with decreased survival. Low-grade inflammation mainly mediated the association of FEV1 with cardiovascular mortality. Highlights: Lung function parameters were inversely associated with low-grade inflammation. Lung function decline was associated with a high total and cardiovascular mortality. Low-grade inflammation mediates the link between FEV1 and cardiovascular mortality.